Pengaruh Struktur Aktiva Dan Profitabilitas Terhadap Struktur Modal (Studi Kasus PT Ultrajaya Milk Industry and Trading Company Tbk. Tahun 2009-2018) - Fania Fania; Axel Giovanni (Sains: Jurnal Manajemen dan Bisnis, 2020)
The research was conducted at PT Ultrajaya Milk Industry and Trading Company TBK. As the food and beverage industry as one of the industry that contributes the highest to gross domestic product (GDP) to the sector of processing industry in Indonesia. In 2012, the food and beverage industry contributed 7.14% to GDP in Indonesia. A descriptive quantitative is the type in this study, the analytical technique used in this research is to use various tests namely classical assumptions, T-Test and F-test and coefficient of determination. Using multiple regression analysis is the most appropriate method for the lysis of the influence of asset structure and profitablity on the capital structure of PT Ultrajaya Milk Industry and Trading Company Tbk. From 2009-2018. The impact of independent variables on dependent variables is 74.8% while the remaining 13.6% are described by variables or other factors not incorporated into this model, so it is evident that the independent variables of the assets and profitability structure have had a strong impact on the corporate capital structure of PT Ultrajaya Milk Industry and Trading Company Tbk in year 2009-2018.